2005
DOI: 10.1016/j.worlddev.2005.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization and Participation: The Governance of Common Pool Resources in Nepal’s Terai

Abstract: Summary. -Decentralization has emerged as an important instrument of environmental and development policy in the last two decades. Presumed benefits of environmental policy decentralization depend in significant measure on broad participation in the programs that governments create to decentralize decision making related to resource management. This paper uses data from protected areas in Nepal's Terai to examine who participates in environmental decentralization programs. On the basis of our statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
200
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(214 citation statements)
references
References 33 publications
10
200
1
3
Order By: Relevance
“…In some cases, this type of approach leads to ill-conceived and hasty promotion of community development by external government or nongovernment organizations, which can exacerbate preexisting inequities, often leading to the further concentration of power in the hands of local elite. The resulting outcomes can be quite contrary to stated objectives of conservation and social development (29,30).…”
Section: Drivers Of Reforestationmentioning
confidence: 74%
See 1 more Smart Citation
“…In some cases, this type of approach leads to ill-conceived and hasty promotion of community development by external government or nongovernment organizations, which can exacerbate preexisting inequities, often leading to the further concentration of power in the hands of local elite. The resulting outcomes can be quite contrary to stated objectives of conservation and social development (29,30).…”
Section: Drivers Of Reforestationmentioning
confidence: 74%
“…Much of the observed increase in forest cover has been attributed to the rapid expansion of the community forestry program, which now covers large parts of the middle hills and an increasing proportion of the Terai plains (20). Yet concerns also have been expressed regarding the rapid expansion of this program, the top-down approach taken toward its implementation, and the heterogeneous nature of its impacts on forests and local communities (18,20,30). Much of this concern can be attributed to the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with the metaanalysis study of Porter-Bolland et al (2012) which emphasizes that across the tropics, local people livelihoods dependence on forest resources was not taken into account in resources conservation initiatives and that local people's rights were neither acknowledged nor secured. Acknowledging and securing local people's rights passed through an effective decentralization mechanism over the management of forest resources (Agrawal and Gupta, 2005). In case of Gabon, a decentralization policy exists.…”
Section: Evaluation Of the Effectiveness Of Governance Over Forest Anmentioning
confidence: 99%
“…Question then, turns to why those residing closer to RCNP who are poorer section in the society that are most vulnerable to biodiversity conservation not attended adequately? From their study in their national park of Nepal, Agrawal and Gupta (2002) reported that richer and upper caste households have a higher probability of joining and participating in government sponsored common property resource management programs. We also observed that those who participate by virtue of economic and caste status have more bargaining power than the poor in the same society.…”
Section: Equity Concerns In Biodiversity Conservationmentioning
confidence: 99%